Merintis Literasi Masyarakat Melalui One Home One Library di Kelurahan Sukoharjo Jawa Tengah - Muhlis Fajar Wicaksana; Titik Sudiatmi; Wahyu Dini Septiari (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This community service aims to realize the RW Literacy Village. 01 Sukoharjo Village through the One Home One Library Community Literacy Movement. Partners The target of this service is the RW. 01 Kelurahan Sukoharjo consists of 4 neighborhood units (RT), starting from RT. 01 to RT. 04. The method of implementing community service activities is through socialization of the establishment of literacy villages, reading week activities with children and youth in the neighborhood, internet surfing week, and digital literacy trainings. The result of this service activity is to provide social change in the RW. 01 Kelurahan Sukoharjo is good in the fields of education, lifestyle, and improving the literacy culture of the community.